The Effect of Heparin and Other Exogenous Glycosaminoglycans (GAGs) in Reducing IL-1β-Induced Pro-Inflammatory Cytokine IL-8 and IL-6 mRNA Expression and the Potential Role for Reducing Inflammation - Murtaza Jafri; Lin Li; Binhua Liang; Ma Luo (MDPI AG, 2024)
Glycosaminoglycans (GAGs) are long linear polysaccharides found in every mammalian tissue. Previously thought only to be involved in cellular structure or hydration, GAGs are now known to be involved in cell signaling and protein modulation in cellular adhesion, growth, proliferation, and anti-coagulation. In this study, we showed that GAGs have an inhibitory effect on the IL-1β-stimulated mRNA expression of IL-6 and IL-8. Exogenous heparin (p < 0.0001), heparan (p < 0.0001), chondroitin (p < 0.049), dermatan (p < 0.0027), and hyaluronan (p < 0.0005) significantly reduced the IL-1β-induced IL-8 mRNA expression in HeLa cells. Exogenous heparin (p < 0.0001), heparan (p < 0.0001), and dermatan (p < 0.0027) also significantly reduced IL-1β-induced IL-6 mRNA expression in HeLa cells, but exogenous chondroitin and hyaluronan had no significant effect. The exogenous GAGs may reduce the transcription of these inflammatory cytokines through binding to TILRR, a co-receptor of IL-1R1, and block/reduce the interactions of TILRR with IL-1R1.